Effectiveness of Pancasila Education Learning Media Using Google Sites Based on Problem-Based Learning in Fifth Grade - Isky, Puja Laila; Reinita, Reinita; Amini, Risda; Ladiva, Hasmai Bungsu (Journal of Educational Sciences, 2025)
The purpose of this research was to assess the effectiveness of learning media developed using Google Sites, which is integrated with the Problem-Based Learning model, in enhancing students' learning outcomes in Pancasila Education. Following the implementation phase, the evaluation stage of the ADDIE model was conducted. The effectiveness was tested using pre-tests and post-tests aligned with relevant learning indicators. The participants were fifth-grade students from three elementary schools: SDN 12 V Koto Kampung Dalam, SDN 19 V Koto Kampung Dalam, and SDN 01 V Koto Kampung Dalam. At SDN 12, the average score improved from 59.09% to 90.00%, with an N-Gain of 0.77 (moderate). At SDN 19, scores increased from 64.07% to 95.93%, with an N-Gain of 0.89 (high). At SDN 01, results rose from 60.00% to 93.33%, with an N-Gain of 0.84 (high). All students achieved the minimum competency standard. These results demonstrate that the developed media is effective in enhancing students’ understanding and mastery of Pancasila Education. The integration of technology and student-centered learning approaches contributes significantly to learning success. Therefore, this Google Sites-based media is considered feasible and recommended as an alternative instructional tool in elementary school learning environments.